2020
DOI: 10.1002/jac5.1331
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing pharmacists to address the opioid crisis: A joint opinion of the ambulatory care and adult medicine practice and research networks of the American College of Clinical Pharmacy

Abstract: The opioid crisis represents one of the largest failures of our current health care system as it continues to claim lives at an unprecedented rate and has caused a devastating range of preventable morbidity. Although the availability of highly potent synthetic opioids has amplified the urgency of the crisis for patients and communities, this problem has evolved over several decades. Pharmacists are in a position to offer many potential solutions due to their widespread accessibility, extensive drug knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 161 publications
(316 reference statements)
0
12
0
Order By: Relevance
“…Another programmatic systems approach to medication management endeavors to create a shared mental model using drug stewardship as a platform of organizational change [ 104 , 105 , 106 , 107 ]. While most stewardship programs have concentrated on rational antimicrobial use [ 108 ], recent developments have focused attention on medication classes that are frequently used in perioperative care and are high-risk for the patient, including opioids [ 109 , 110 , 111 , 112 , 113 ], anticoagulants [ 114 , 115 , 116 , 117 , 118 , 119 , 120 ], anemia management [ 121 , 122 , 123 , 124 , 125 ], and glycemic control with insulin [ 126 , 127 ], among others [ 4 ]. Table 5 summarizes recommendations for preventing VTE, SSI, PONV, POI, and PoD [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another programmatic systems approach to medication management endeavors to create a shared mental model using drug stewardship as a platform of organizational change [ 104 , 105 , 106 , 107 ]. While most stewardship programs have concentrated on rational antimicrobial use [ 108 ], recent developments have focused attention on medication classes that are frequently used in perioperative care and are high-risk for the patient, including opioids [ 109 , 110 , 111 , 112 , 113 ], anticoagulants [ 114 , 115 , 116 , 117 , 118 , 119 , 120 ], anemia management [ 121 , 122 , 123 , 124 , 125 ], and glycemic control with insulin [ 126 , 127 ], among others [ 4 ]. Table 5 summarizes recommendations for preventing VTE, SSI, PONV, POI, and PoD [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Opportunities and challenges exist for pharmacists to play a larger role in mitigating problems associated with harmful use of opioids including distributing safe in-home disposal products for opioids. 37 Clayton Christensen and colleagues 38 wrote that innovation always pushes solutions closer to the consumer. Innovative in-home opioid disposal products or systems can optimize patient access to opioid disposal solutions and facilitate elimination of unused opioids from patients' homes as long as sufficient financial and technology resources are provided at the point of care for patients.…”
Section: Pharmacist Patient Care and Services: A Call To Actionmentioning
confidence: 99%
“…In October 2017, the Acting Secretary of Health and Human Services declared the opioid epidemic a public health emergency ( 1 ). Since then, national pharmacy organizations have banded together to empower pharmacists to take an active and preventive role in addressing the opioid crisis ( 2 , 3 ). In 2018, North Dakota reported that more than half of all drug overdose deaths were attributable to opioids ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists in various practice settings have taken steps to prevent opioid misuse and accidental overdose ( 3 , 6 , 7 ). These steps include evaluating program information on prescription drug monitoring, dispensing naloxone, referring patients for substance use disorder treatment, and enhancing patient and pharmacist education ( 8 11 ).…”
Section: Introductionmentioning
confidence: 99%